Photo-reduction of Carbon Dioxide Using Zns Supported Kaolin in a Photo Catalytic Batch Reactor System - Tengku Mohd Nurul Naim, Tengku Jaapar (2013)
Carbon dioxide (CO2) accounts for the largest share of the world’s greenhouse gas emissions. There is a growing need to mitigate CO2 emissions. Some of the strategies to mitigate CO2 emissions are energy conservation, carbon capture and storage and using CO2 as a raw material in chemical processes. One of the best routes to remedy CO2 is reduce the concentration of CO2 is transforming-it to biofuels via photo reduction process. In this study, CO2 is photocatalytically reduced to produce methanol using ZnS supported kaolin in a photo-catalytic batch reactor assisted by UV lamp. The potential application of photocatalysis is to remove or mitigate a wide range of global warming contributors from the atmosphere. By harnessing UV light, photocatalytic process consumes less energy than conventional methods. The synthesis of heterogeneous catalyst from low cost materials was studied in order to produce valuable product which is methanol. The paramaters that affect the reaction such as effect of dosage and reaction time was studied. From this study, the methanol yield will be increased when there is an increasing of the dosage of catalyst used. The yields of product was analysed by using High Performance Liquid Chromatography (HPLC). In this study, it have been prove that the higher amount of dosage catalyst used may give high methanol yield. The 2.0 g ZnS-Kaolin catalyst that used in the photo-reduction process have produced the highest of methanol yield which is 70.5 ng/µL.